Engineering triangular carbon quantum dots with unprecedented narrow bandwidth emission for multicolored LEDs - Fanglong Yuan (Nature Portfolio, 2018)
Carbon quantum dots have promising advantages such as high stability, low cost and environment-friendliness, but their broad emission band limits their application in displays. Here Yuan et al. synthesize these dots showing tunable emission color, high fluorescence and a narrow FWHM of only 30 nanometers.